Impact of Resistance to Fluconazole on Virulence and Morphological Aspects of Cryptococcus neoformans and Cryptococcus gattii Isolates - Rossi, Suélen A.; Trevijano-Contador, Nuria; Scorzoni, Liliana; Mesa-Arango, Ana Cecilia; de Oliveira, Haroldo C.; Werther, Karin; de Freitas Raso, Tânia; Mendes-Giannini, Maria J. S.; Zaragoza, Oscar; Fusco-Almeida, Ana M. (Frontiers in Microbiology, 2016)
Cryptococcus spp. are responsible for around one million cases of meningitis every year. Fluconazole (FLU) is commonly used in the treatment of cryptococcosis, mainly in immunocompromised patients and the resistance is usually reported after long periods of treatment. In this study, the morphological characterization and virulence profile of FLU-susceptible and FLU-resistant clinical and environmental isolates of C. neoformans and C. gattii were performed both in vitro and in vivo using the Galleria mellonella model. FLU-susceptible isolates from C. neoformans were significantly more virulent than the FLU-resistant isolates. FLU-susceptible C. gattii isolates showed a different virulence profile from C. neoformans isolates where only the environmental isolate, CL, was more virulent compared with the resistant isolates. Cell morphology and capsule size were analyzed and the FLU-resistant isolates did not change significantly compared with the most sensitive isolates. Growth at 37°C was also evaluated and in both species, the resistant isolates showed a reduced growth at this temperature, indicating that FLU resistance can affect their growth. Based on the results obtained is possible suggest that FLU resistance can influence the morphology of the isolates and consequently changed the virulence profiles. The most evident results were observed for C. neoformans showing that the adaptation of isolates to antifungal selective pressure influenced the loss of virulence.